Percepción de los factores de riesgo y protección en un grupo de madres frente al embarazo adolescente: un análisis antes, durante y después del embarazo (2017)
The objective of the present investigation is to describe the perception of the risk factors and protection of the nursing mothers belonging to the unit My First Steps of the CDI Manos Unidas Family Modality, located in the locality Rafael Uribe with respect to their adolescent pregnancy, A qualitative study, developed in 3 stages, is initially performed with the lactating mothers of the locality who meet the criteria for this research, 8 mothers between the ages of 14 and 19 are selected to whom the semi-structured interview is applied; In stage 2 the transcription and systematization of the information is developed through the program Atlas-ti; from this, the analysis of the content matrix that is obtained from the systematization, we conclude that the risk factors and the protection factors have a significant contrast with the theory since it is a problem that has been worked In previous occasions maintaining high birth rates in pregnancies at an early age.